OpenAIRE Guidelines for Data Archive Managers v1.0 - Elbaek, Mikael; Nielsen, Lars Holm (Zenodo, 2013)
OpenAIRE gathers together research output related to European funding streams, with the aim of supporting open science and tracking research impact. This content consists of open access publications and related contextual information such as datasets, supplementary material, and research/project information. Two other sets of OpenAIRE guidelines exist for repository managers: OpenAIRE Guidelines for Literature Repositories 3.0 OpenAIRE Guidelines for CRIS systems (CERIF standard) – In draft The OpenAIRE Guidelines for Data Archive Managers 1.0 provides instruction for data archive managers to expose their metadata in a way that is compatible with the OpenAIRE infrastructure. The metadata from data archives should be included in the OpenAIRE information space, and exposed when data are related to an open access publication e.g. a dataset cited by an article. By implementing the OpenAIRE Guidelines data archive managers are facilitating the creation of enhanced publications and building the stepping-stones for a linked data infrastructure for research. Exposure and visibility of content from a range of European repositories will be significantly increased when a common and interoperable approach is taken and care to adhere to existing guidelines. OpenAIRE is happy to assist in adherence to these guidelines. This compatibility will lead to future interoperability between research infrastructures, and structured metadata is of benefit to individual data repositories and the scholarly community at large.